How to Build Online Consumer Trust in an Islamic Perspective Through TikTok Live Streaming Shopping - Fadhilah Fadhilah; Galih Ginanjar Saputra; Tri Wahyudi; Muhamad Fakhrudin (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
This research aims to explore the importance of paying attention to Islamic values in marketing activities and how to choose streamers of TikTok live streaming who are by the Sharia perspective as well as effective marketing techniques to build consumer trust and consumer purchase decisions. The data analysis method used in this study is an interactive data analysis model developed by Miles and Huberman. Data analysis for qualitative purposes is carried out interactively. Based on the results and discussions described earlier, it can be concluded that Islamic values related to the five guidelines of muamalah play an important role in building consumer trust and purchase decisions in TikTok live streaming shopping in Indonesia. There has been no research that uses the 5 Muamalah Guidelines approach in using TikTok Live Streaming Shopping in Indonesia. The subjects studied were only respondents who had followed live-streaming shopping on the TikTok platform in Indonesia. This research has implications for entrepreneurs who want to sell their products through live streaming on the TikTok platform. Principle 5 Muamalah guidelines can not only be applied in social life but also need to be internalized in business activities.